Effects of Controlled Breathing Maneuver on Exercise Tolerance in Patients with Chronic Obstructive Pulmonary Disease - Saira Ali, Zainab Hassan, Anum Khalid, Bilal Ahmad, Mahat Zahra, Mishal Gul (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic obstructive pulmonary disease, which is usually caused by harmful particles or gases, is associated with persistent respiratory symptoms. Aim: To determine effects of controlled breathing techniques for respiratory muscle strengthening and functional capacity. Study Design: Randomized control trial. Methodology: Study was conducted at Services Hospital Lahore for duration of 6months. Patients (n=48) were enrolled through convenient sampling. Participants were divided into two groups 24 in each group. Both groups A and B received baseline treatment for pulmonary rehabilitation. Pursed lip breathing technique was performed to group B, 20 minutes session for 4 days per week. Pre and post treatment readings were taken and the results were analyzed. Informed consent was taken. Data was evaluated by using SPSS vr 23. Before and after comparison was made using paired sample t test considering normality of data. Results: Almost 18.75% were in the age range of (40-49 years), 16(33.33%) in (50-59), 10(20.83%) in (60-69) and 13(27.08%) in (70-75). The pre and post readings showed that there was a mean difference in 6MWT and AQ20 with significant p-value. Conclusion: It was concluded that controlled breathing techniques have been found to be more effective to increase exercise tolerance in people with chronic obstructive pulmonary disease. Keywords: chronic obstructive pulmonary disease, Exercise Tolerance, Controlled Breathing Maneuvers and Pulmonary Functions.